Language Style Analysis in the Short Film ‘The Mourning Bird’ - Fista Elma Ratu Indayani; Abdul Muhid; Agus Syahid; Titik Ceriyani Miswaty; Ni Ketut Putri Nila Sudewi (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study explores the use of language style in the short film The Mourning Bird by applying Martin Joos’ theory of five language registers: frozen, formal, consultative, casual, and intimate. Using a qualitative descriptive approach, the analysis focuses on identifying and classifying the types of language styles present in the film, and determining which style is most dominant. The dialogues are examined based on their level of formality and the context in which they occur, with attention to how each style contributes to character development and emotional expression. The findings reveal that casual and intimate styles are most frequently used, reflecting the film’s focus on family relationships, grief, and interpersonal tension. This study confirms that language style plays a critical role in short-form storytelling and supports the application of stylistic theory in film and media studies. The insights from this research may benefit linguists, educators, and filmmakers interested in narrative strategy and character portrayal through language..